Sexual Dimorphism in Immune Development and in Response to Nutritional Intervention in Neonatal Piglets - Christoforidou, Zoe; Mora Ortiz, Marina; Poveda, Carlos; Abbas, Munawar; Walton, Gemma; Bailey, Michael; Lewis, Marie C. (Frontiers in Immunology, 2019)
Although gender disparity in immunological function and susceptibility to various inflammatory and infectious disease is recognised in adults, far less is known about the situation in young infants during immune development. We have used an outbred piglet model to explore potential early gender disparity underlying both mucosal immune development and systemic responses to novel antigen. Despite similarities in intestinal barrier function and therefore, presumably, antigen exposure, females had less CD172+ (Sirp-) antigen presenting cells and expression of MHCIIDR at 28 days old compared to males, along with greater regulatory T-cell numbers. This suggests that, during infancy, females may have greater potential for local immune regulation than their male counterparts. However, females also presented with significantly greater systemic antibody responses to injected ovalbumin and dietary soya. Females also synthesised significantly more IgA in mesenteric lymph nodes, whereas males synthesised more in caecal mucosa, suggesting that plasma cells were retained within the MLN in females, but increased numbers of plasma cells circulated through to the mucosal tissue in males. Significant effects of inulin and B. lactis NCC2818 on the developing immune system were also gender-dependent. Our results may start to explain inconsistencies in outcomes of trials of functional foods in infants, as distinction between males and females is seldom made. Since later functionality of the immune system is highly dependent on appropriate development during infancy, stratifying nutritional interventions by gender may present a novel means of optimising treatments and preventative strategies to reduce the risk of the development of immunological disorders in later life.